POLYGAMY IN INDONESIAN ISLAMIC FAMILY LAW - Nasution, Khoiruddin (Jurnal Syariah, 2008)
There were four main aims of the emergence of Marriage Law No. 1 of 1974. First of all, to restrict or even abolish child marriage; secondly, to restrict polygamy; thirdly, to restrict the one-sided right of repudiation (talaq); and lastly, to establish equal rights for husbands and wives. In addition, the enactment (rule/Government Regulation/Peraturan Pemerintah [PP] No. 10 of 1983 was also at the request of Dharma Wanita (Official Sisterhood). Even though the number of wives of highranking officials of Dharma Wanita was small, they were quite influential. They claimed that their organization had received many complaints from members about their husbands’ behaviour dealing with divorce, polygamy and lack of financial support. Consequently, they demanded a law to protect them from polygamy and divorce. This paper describes the status of polygamy in the Indonesian Islamic Family Law, in particular as it has been promulgated in Marriage Law No. 1 of 1974, Rule No. 9 of 1975, Rule No. 10 of 1983, and its comparison with other Islamic Family Law in the contemporary. The main sources of the research are Marriage Law No. 1 of 1974, Rule No. 9 of 1975, and Rule No. 10 of 1983. It is found that Indonesian Islamic Family Law is included in the group that restricts the possibility of polygamy with some variations. This group includes the majority of Muslim countries. Turkey, Tunisia and that Druze Sect in Lebanon, are the only countries which prohibit polygamy completely. Furthermore, concern for the application of laws and its effect to social life are still debatable among scholars. Some scholars view that it gives a positive effect, while others do not.